AN ANALYSIS OF GRAMMATICAL COHESION IN COVID-19 NEWS OF THE JAKARTA POST - Larassati, Indah; Qomar, Aulia Hanifah; Darmawan, Syaifudin Latif (Journal of English Education and Enterpreneurship (JEEP), 2021)
Grammatical cohesion is the combination of sentences that formed by grammatical aspect. Language can produce two kinds there are spoken and written The objectives of this research are to describe the types of reference and subtitution and discover the most frequently types of reference and subtitution that used in The Jakarta Post news. Grammatical cohesion is the object of this research. The news in The Jakarta Post is the subject of this research. The method of this research is Qualitative research. The result of this study are found 436 of grammatical cohesion consist of reference were 434 data, and substitution are 2 data. The most frequently types of using grammatical cohesion is demonstrative reference with the percentage 60.80% of. The used of grammatical cohesion are personal reference showed of 27.80 % data, comparative reference showed of 11% data, nominal substitution showed of 0.20% data, verbal substitution found of 0.20% data and causal substitution with the percentage 0%. Based on the data it can be concluded that in The Jakarta Post found all the grammatical cohesion except causal substitution.